Implementasi Program Kewirausahaan Sebagai Upaya Membangun Jiwa Entrepreneur Siswa Di Sekolah SMK Quran Darul Ma'arif - Lestari, Neni; Usrotussaidah, Zahrah; Novaldo, Sandi; Hendrianto (LPPM STIE Tri Dharma Nusantara - Makassar, 2025)
This study examines the entrepreneurship program at SMK Quran Darul Ma’arif, which aims to build students’ entrepreneurial spirit through project-based learning, real production activities, internships, and social-managerial skills training. The program integrates Islamic values as the foundation of business ethics, ensuring students gain both practical skills and religious-based character. Activities such as actual production and marketing including agribusiness enhance creativity, risk-taking, and independence. Although challenges like limited resources and industry support exist, ongoing evaluations help maintain program effectiveness. Qualitative findings show significant improvement in students’ entrepreneurial attitudes and abilities. With teacher guidance, adequate facilities, and a structured entrepreneurial ecosystem, the program successfully prepares students to become independent entrepreneurs who uphold Islamic values.